A staff development program for public librarians in the National Capital Region, Philippines - Berdin, Glen P. 1969-
Of the 17 public libraries in the National Capital Region, 46 respondents ranging from the position of Librarians I to V qualified as subjects of the study. Of this number, 34 (74 percent) are within the bracket of Librarian I and II. It was found that the gap in educational preparation between library science and non-library science graduates is a slim 6 percent, in spite of the fact that 13 percent of the population are undergraduates. The study also revealed that the greater part of the population, 36(78 percent) have worked for decades in the library, and 24 (52 percent) have been performing their job very well over the years. A total of 14 (30 percent) are licensed while the rest are not. The respondents expressed their interest regarding topics that they think should be included in a staff development program. It was also found that among the variables tested, only B (position) and F (performance) have a significant correlation at .288 level. This means that there is a slight correlation, definite but small relationship. Variable E (licensure examination) and G(perormance rating) have a significant correlation at .180 level, meaning there is a slight, almost negligible correlation. The proposed needs-based staff development would divide the participants into two groups to separate personnel more inclined to learn vital library functions from those who are inclined to learn management functions. Pre-training questionnaires should also be distributed for evaluation purposes and as basis for improved conduct of future training.